Marine Natural Products: A Promising Source of Environmentally Friendly Antifouling Agents for the Maritime Industries - Gomez-Banderas, Jessica (Frontiers in Marine Science, 2022)
Biofouling in the marine environment refers to an unwanted build-up of marine organisms on subsea surfaces including harbour docks, hulls of ships and offshore installations. The first stage of marine fouling occurs as a microbial biofilm which forms via the aggregation of bacterial, algal and fungal cells. This biofilm provides a favourable substrate for the larval settlement of larger organisms such as mussels, barnacles and hard corals which accumulate to uncontrollable extents, causing issues for the maritime industries. Since the ban of tributyltin (TBT) in 2008 by the International Maritime Organisation, alternative antifouling agents have been used such as algaecides and copper-based coatings. Recent studies are showing that these can accumulate in the marine environment and have toxic effects against non-target species. Marine microbes and invertebrates are known to be prolific producers of bioactive molecules, including antifouling active compounds. These compounds are often produced by marine organisms as a means of chemical defence to deter predators and prevent fouling of their own surfaces, making them a promising source of new antifouling agents. This article discusses the effects of biofouling on the maritime industries, the environmental dangers of currently used antifouling compounds and why natural products from marine organisms could be a source of environmentally friendly antifouling agents.